Maltose as an Ecofriendly Modifier of the Buried Interface for Efficient and Stable Inverted Perovskite Solar Cells. Issue 9 (5th July 2022) - Yang, Boping; Pan, Yili; Ding, Yu; Ouyang, Dan; Zhang, Hong
Abstract : A new concept of modifying the buried interface with ecofriendly material to improve the photovoltaic performance of inverted perovskite solar cells (PSCs) is proposed. A low‐cost and ecofriendly maltose with multihydroxyl groups is facilely chosen for the proof of our concept. The maltose modification not only improves the hole mobility of hole transporting layer, but also regulates the formation of a high‐quality perovskite film with a low density of gain boundary and trap states. The resulting inverted PSCs show a champion power conversion efficiency of 20.65% with negligible hysteresis, accompanied by enhanced thermal and operational stability. This work shows that buried interface engineering with ecofriendly materials opens a new avenue to further improve the efficiency and stability of sustainable PSCs. Abstract : A low‐cost and ecofriendly maltose is developed to modify the buried interface and regulate the crystallization and formation of a perovskite film with less density of trap states. As a result, the resulting inverted perovskite solar cells show a champion power conversion efficiency of 20.65%, accompanied by enhanced thermal and operational stability.